THE ROLE AND FUTURE OF G8 - Omer, Soran Kakarash (Journal of process management and new technologies, 2019)
The Group of Eight (G8) or the G-8 is the world's major economic powers. This paper is an attempt to appear the role of world's future. As well as, the research as an theoretical trying to increase information and knowledge about the G8 in terms of the conception and nature, as well as increasing the knowledge of how to create and the goals and aspirations of the group and determine its future, also it was based on the descriptive approach by examining the nature of the roles played by the international organizations and the global conglomerates. In conclusion, establishment and future of the G8 is two belongings that are sensitive to energy sources, especially oil and its prices. Keywords: Group of Eight (G8), Informal organization.